A method for preparing a copper-based composite powder reinforced by nanometer copper-coated graphene nanosheets

CN116329543BActive Publication Date: 2026-10-30HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310156402.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2026-10-30
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

[0005]本发明为了解决现有的石墨烯在铜基体中易团聚以及石墨烯-铜复合粉末的制备方法存在均匀性差、效率低、结合强度低和易产生环境污染的问题,提出一种纳米铜包覆石墨烯纳米片增强铜基复合粉末制备方法

Benefits of technology

[0013]1、本发明以改进的磁控溅射颗粒搅拌装置进行竖直平面磁控溅射,制备出纳米铜包覆石墨烯纳米片粉末颗粒作为增强颗粒,同时采用低能球磨工艺制备出铜基复合粉末,其中,磁控溅射颗粒搅拌装置中搅拌叶片和硬质刷毛可使待镀粉末进行充分搅拌,挡板可限制搅拌过程中研磨球的位移,有利于防止待镀粉末的团聚和堆积。采用磁控溅射颗粒搅拌装置使得沉积速率提高,铜膜层包覆均匀,纳米铜与石墨烯纳米片粉末结合强度高;磁控溅射过程加入的研磨球及搅拌作用可有效抑制石墨烯的团聚的同时显著增加石墨烯纳米片粉末的被溅射表面,几乎石墨烯纳米片粉末的全部外表面都能被铜包覆,因而,其与纯铜粉末颗粒结合效果好,在复合粉末中不易发生石墨烯与铜粉末的分离。从而制备出一种具备优异热电、机械、耐磨损、耐腐蚀的复合粉末。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116329543B_ABST
    Figure CN116329543B_ABST
Patent Text Reader

Abstract

The application relates to a preparation method of copper-based composite powder, and discloses a preparation method of copper-based composite powder. In order to solve the problems that existing graphene is easy to agglomerate in a copper matrix, the preparation method of graphene-copper composite powder has poor uniformity, low efficiency, low bonding strength and is easy to cause environmental pollution, the vertical plane magnetron sputtering technology is introduced, the improved magnetron sputtering particle stirring workpiece device is used to grow copper on the surface of graphene nanosheet powder, copper-coated graphene nanosheet powder is obtained, copper coating on almost all the outer surfaces of the graphene nanosheet powder can be realized, an optimized low-energy ball milling process is used, the copper-coated graphene nanosheet powder is uniformly distributed in the composite powder of copper powder, graphene agglomeration is effectively avoided, and excellent thermoelectric, mechanical, wear resistance and corrosion resistance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing copper-based composite powder reinforced with copper nanosheets coated with graphene nanosheets. Background Technology

[0002] The application scenarios for various materials such as metals, plastics, fibers, and rubber are expanding. These materials are prone to generating static electricity, which can easily cause electromagnetic interference, electrical breakdown, and even serious accidents such as fires. To prevent static electricity generation, conductive powders are often added to various materials to impart conductivity. Composite conductive powders are widely used in electronics, communications, chemicals, shipbuilding, military, and aerospace industries. Pure copper powder has excellent electrical and thermal conductivity, but its hardness and wear resistance are poor, making it susceptible to severe wear and corrosion in complex service environments such as electrical, chemical, and atmospheric conditions. This causes the conductive coating formed to easily peel off, resulting in serious safety hazards and economic and personnel losses.

[0003] Graphene is a two-dimensional allotrope of carbon, formed by the hybridization of 1-s and 2-p orbitals, resulting in hexagonal carbon rings. In graphene, each carbon atom, after sp2 hybridization, possesses a free electron, which resides in the π orbital. The π orbital facilitates the dislocation of the electron network and couples high carrier (electron) concentration with high carrier mobility at room temperature. These unique properties of graphene enable localized carrier conduction to reach near-micrometer scales, and its excellent mechanical, wear-resistant, and corrosion-resistant properties make it an ideal additive for improving the thermoelectric, mechanical, wear-resistant, and corrosion-resistant properties of metals. Copper materials reinforced with graphene exhibit significantly improved thermoelectric, mechanical, wear-resistant, and corrosion-resistant properties. However, due to graphene's large specific surface area and high surface energy, it is prone to aggregation, hindering uniform dispersion within the copper matrix.

[0004] Physical vapor deposition (PVD) is a gas deposition process that uses physical methods under vacuum conditions to vaporize a material source (solid or liquid) into gaseous atoms or molecules, or partially ionize them into ions, and then deposits a thin film with specific functions onto a substrate surface through a low-pressure gas (or plasma) process. This process includes three main categories: vacuum evaporation, magnetron sputtering, and arc ion plating. The resulting films are uniform and dense, with high bonding strength between the film and the substrate. The process is simple and pollution-free. Because film deposition can be achieved on any surface in contact with gaseous atoms, molecules, or ions, PVD also exhibits good film deposition effects on complex geometric surfaces. Traditional methods for preparing graphene-copper composite powders include high-speed ball milling, chemical vapor deposition, and chemical growth. High-speed ball milling results in poor coating uniformity, long processing time, and low bonding strength between graphene and copper particles. The composite powder is prone to stratification under gravity after ball milling. Chemical vapor deposition has extremely low production efficiency and is difficult to achieve mass production of mixed powders. Chemical growth requires the use of various chemical reagents, is complex to operate, and is prone to causing environmental pollution. Summary of the Invention

[0005] To address the problems of easy agglomeration of graphene in a copper matrix and the poor uniformity, low efficiency, low bonding strength, and environmental pollution associated with existing graphene-copper composite powder preparation methods, this invention proposes a method for preparing copper-based composite powder reinforced with copper nanosheets.

[0006] This invention introduces vertical planar magnetron sputtering technology. Using an improved magnetron sputtering particle stirring device, copper is grown on the surface of graphene nanosheet powder to obtain copper-coated graphene nanosheet powder. This can achieve copper coating on almost the entire outer surface of the graphene nanosheet powder. Using an optimized low-energy ball milling process, the obtained copper-coated graphene nanosheet powder is uniformly distributed in the copper powder composite powder, effectively avoiding graphene agglomeration and exhibiting excellent thermoelectric, mechanical, wear-resistant, and corrosion-resistant properties.

[0007] The preparation method of the copper-coated graphene nanosheet-reinforced copper-based composite powder of the present invention is carried out according to the following steps:

[0008] Step 1: Deposit a copper nanofilm on the surface of graphene nanosheets using a magnetron sputtering device to obtain copper nanocoated graphene nanosheet powder.

[0009] The magnetron sputtering device comprises a vacuum chamber, a magnetron sputtering particle stirring device, a heater, and a magnetron sputtering target. A magnetron sputtering target is mounted on the top of the vacuum chamber, connected to the top wall of the vacuum chamber via a magnetron sputtering target telescopic rod. An air inlet and an air outlet are respectively located on a pair of opposite side walls within the vacuum chamber. A heater is mounted on the side wall of the vacuum chamber above the air inlet and outlet, connected to the side wall of the vacuum chamber via a heater telescopic rod. The magnetron sputtering target is located on the top of the vacuum chamber, connected to the lower top surface of the vacuum chamber via a magnetron sputtering target telescopic rod. The magnetron sputtering particle stirring device is located on the inner bottom surface of the vacuum chamber and comprises a detachable tray, stirring blades, a strip baffle, rigid bristles, a positioning rod, a central shaft, and a connecting shaft. The system consists of: a detachable storage tray with a retaining edge around its upper surface and a boss at its center; several stirring blades are radially fixed horizontally to the side wall of a central shaft, which is located on the upper surface of the boss; a vertical through hole at the center of the boss; a connecting shaft inside the through hole, with its upper end connected to the central shaft and its lower end connected to the power output shaft of the drive motor; several strip-shaped baffles on the lower surface of each stirring blade, with the length of the baffles gradually decreasing from the tip of the stirring blade to the central shaft; rigid bristles arranged in a straight line between two adjacent strip-shaped baffles on the lower surface of the stirring blade; and several positioning rods below the detachable storage tray, with the upper end of each rod positioned in a positioning hole on the lower surface of the detachable storage tray and the lower end fixed to the bottom of the vacuum chamber.

[0010] Step 2: Use a ball mill to perform low-energy ball milling on the nano-copper-coated graphene nanosheet powder and copper powder to obtain nano-copper-coated graphene nanosheet-reinforced copper-based composite powder.

[0011] Step 2, the low-energy ball milling process, is as follows: copper powder and copper nano-coated graphene nanosheet powder are mixed at a mass ratio of 4 to 19:1 and then loaded into a ball mill jar; first, a vacuum is drawn, and then argon gas is introduced. The ball milling process is dry milling, the ball-to-material ratio is 8 to 12:1, the ball milling speed is 50 to 200 r / min, the ball milling time is 4 to 10 h, unidirectional rotation, and a 10 min stop after every 1 h of ball milling.

[0012] The principle and beneficial effects of this invention are as follows:

[0013] 1. This invention utilizes an improved magnetron sputtering particle stirring device for vertical planar magnetron sputtering to prepare copper-coated graphene nanosheet powder particles as reinforcing particles. Simultaneously, a low-energy ball milling process is employed to prepare a copper-based composite powder. The stirring blades and hard bristles in the magnetron sputtering particle stirring device ensure thorough stirring of the powder to be deposited, while the baffle restricts the displacement of the grinding balls during stirring, preventing agglomeration and accumulation of the powder. The magnetron sputtering particle stirring device increases the deposition rate, results in a uniform copper film coating, and demonstrates high bonding strength between the copper nanosheets and graphene nanosheet powder. The grinding balls and stirring action during magnetron sputtering effectively suppress graphene agglomeration while significantly increasing the sputtered surface area of ​​the graphene nanosheet powder. Almost the entire outer surface of the graphene nanosheet powder is coated with copper, resulting in good bonding with pure copper powder particles and minimizing separation between graphene and copper powder in the composite powder. This leads to the preparation of a composite powder with excellent thermoelectric, mechanical, wear-resistant, and corrosion-resistant properties.

[0014] 2. This invention utilizes graphene, which has excellent electrical, mechanical, and wear-resistant properties. The copper-coated graphene nanosheets reinforced copper-based composite powder obtained by combining magnetron sputtering and low-energy ball milling can effectively improve the bonding strength between graphene and copper powder, and enable graphene to be uniformly distributed in the copper powder. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the magnetron sputtering device in Example 1. In the figure, a is a grinding ball and b is the powder to be deposited.

[0016] Figure 2 This is a top view of the stirring blade 2 and baffle 3 in the magnetron sputtering device of Example 1;

[0017] Figure 3 This is an EDS image of the Cu elemental distribution in the copper-coated graphene nanosheet powder from Example 1.

[0018] Figure 4 The image shown is an SEM image of the composite powder sample prepared in Example 1. Detailed Implementation

[0019] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any reasonable combination of the specific embodiments.

[0020] Specific Implementation Method 1: The preparation method of copper-coated graphene nanosheets reinforced copper-based composite powder in this implementation method is carried out according to the following steps:

[0021] Step 1: Deposit a copper nanofilm on the surface of graphene nanosheets using a magnetron sputtering device to obtain copper nanocoated graphene nanosheet powder.

[0022] The magnetron sputtering device comprises a vacuum chamber, a magnetron sputtering particle stirring device, a heater 13, and a magnetron sputtering target 15. The magnetron sputtering target 15 is mounted on the top of the vacuum chamber and is connected to the top wall of the vacuum chamber via a magnetron sputtering target telescopic rod 14. An air inlet 10 and an air outlet 11 are respectively mounted on a pair of opposite side walls of the vacuum chamber. A heater 13 is mounted on the side wall of the vacuum chamber above the air inlet 10 and the air outlet 11, and is connected to the side wall of the vacuum chamber via a heater telescopic rod 12. The magnetron sputtering target 15 is mounted on the top of the vacuum chamber and is connected to the lower top surface of the vacuum chamber via the magnetron sputtering target telescopic rod 14. The magnetron sputtering particle stirring device is mounted on the inner bottom surface of the vacuum chamber and consists of a detachable tray 1, stirring blades 2, strip baffles 3, hard bristles 4, a positioning rod 6, and a central shaft. The system consists of a 7 and a connecting shaft 8. A retaining edge is provided around the upper surface of the detachable storage tray 1. A boss 9 is provided in the center of the detachable storage tray 1. Several stirring blades 2 are radially and horizontally fixed on the side wall of the central shaft 7. The central shaft 7 is located on the upper surface of the boss 9. A vertical through hole is provided in the center of the boss 9. The connecting shaft 8 is located inside the through hole. The upper end of the connecting shaft 8 is connected to the central shaft 7, and the lower end of the connecting shaft 8 is connected to the power output shaft 5 of the drive motor. Several strip-shaped baffles 3 are provided on the lower surface of each stirring blade 2. The length of the strip-shaped baffles 3 gradually decreases from the end of the stirring blade 2 to the central shaft 7. A straight line of hard bristles 4 is provided between two adjacent strip-shaped baffles 3 on the lower surface of the stirring blade 2. Several positioning rods 6 are provided below the detachable storage tray 1. The upper end of the positioning rod 6 is located in the positioning hole on the lower surface of the detachable storage tray 1, and the lower end of the positioning rod 6 is fixed to the bottom of the vacuum chamber.

[0023] Step 2: Use a ball mill to perform low-energy ball milling on the nano-copper-coated graphene nanosheet powder and copper powder to obtain nano-copper-coated graphene nanosheet-reinforced copper-based composite powder.

[0024] Step 2, the low-energy ball milling process, is as follows: copper powder and copper nano-coated graphene nanosheet powder are mixed at a mass ratio of 4 to 19:1 and then loaded into a ball mill jar; first, a vacuum is drawn, and then argon gas is introduced. The ball milling process is dry milling, the ball-to-material ratio is 8 to 12:1, the ball milling speed is 50 to 200 r / min, the ball milling time is 4 to 10 h, unidirectional rotation, and a 10 min stop after every 1 h of ball milling.

[0025] 1. This embodiment uses an improved magnetron sputtering particle stirring device for vertical planar magnetron sputtering to prepare copper-coated graphene nanosheet powder particles as reinforcing particles. Simultaneously, a low-energy ball milling process is used to prepare a copper-based composite powder. The stirring blades and hard bristles in the magnetron sputtering particle stirring device ensure thorough stirring of the powder to be deposited, while the baffle restricts the displacement of the grinding balls during stirring, helping to prevent agglomeration and accumulation of the powder. The use of the magnetron sputtering particle stirring device increases the deposition rate, results in a uniform copper film coating, and demonstrates high bonding strength between the copper nanosheets and graphene nanosheet powder. The grinding balls and stirring action during the magnetron sputtering process effectively suppress graphene agglomeration while significantly increasing the sputtered surface area of ​​the graphene nanosheet powder. Almost the entire outer surface of the graphene nanosheet powder can be coated with copper, resulting in good bonding with pure copper powder particles and minimizing the separation of graphene and copper powder in the composite powder. This produces a composite powder with excellent thermoelectric, mechanical, wear-resistant, and corrosion-resistant properties.

[0026] 2. In this embodiment, graphene has excellent electrical, mechanical and wear resistance properties. The copper-coated graphene nanosheets reinforced copper-based composite powder obtained by combining magnetron sputtering and low-energy ball milling can effectively improve the bonding strength between graphene and copper powder and enable graphene to be uniformly distributed in copper powder.

[0027] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that the graphene nanosheets described in step one have a purity of 99%, a sheet diameter of 7-10 μm, a thickness of <100 nm, and a bulk density of 0.08-0.13 g / mL.

[0028] Specific Implementation Method 3: This implementation method differs from Specific Implementation Method 1 or 2 in that the lower end of the connecting shaft 8 mentioned in step 1 is connected to the power output shaft 5 of the drive motor by a key.

[0029] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that: the method for depositing a nano-copper film layer on the surface of graphene nanosheets using a magnetron sputtering device in step one is as follows:

[0030] ① Equipment preparation: Connect the pure copper target to the negative terminal of the target power supply, and connect the positive terminal of the target power supply to the vacuum chamber; the sputtering power supply is a DC-coupled high-power pulse power supply, with a DC current range of 0-20A, a pulse frequency range of 10-1000Hz, a pulse width range of 20-1000μs, and a pulse discharge voltage range of 0-2000V; connect the placement tray to the negative terminal of the bias power supply, and connect the positive terminal of the bias power supply to the vacuum chamber. The bias power supply is a medium-frequency power supply with a constant frequency of 40KHz, a pulse width range of 0-24μs, and a voltage range of 0-500V;

[0031] ② Sample preparation: Dry the graphene nanosheet powder in a drying oven, take out the dried graphene nanosheet powder and place it in the detachable tray 1, and add Al2O3 grinding balls to the tray. The mass ratio of powder to grinding balls is 1:8-12.

[0032] ③ Pre-treatment before coating: Evacuate the vacuum chamber to a pressure of 8×10 -3 Heat and dry at 80-150℃ for 10-60 minutes, then evacuate again to a pressure of 8×10⁻⁶ Pa. -3 Pa, introduce working gas to a pressure of 0.1-10 Pa, perform plasma sputtering cleaning for 5-60 min, and set the rotation speed of stirring blade 2 to 5-20 r / min;

[0033] ④ Sputtering coating: Introduce working gas and reactive gas, both with a flow rate of 1-60 sccm. Turn on the power and perform magnetron sputtering coating for 1-3000 min.

[0034] Specific Implementation Method 5: This implementation method differs from Specific Implementation Methods 1 to 4 in that the pure copper target mentioned in step ① is in sheet form and has a purity of 99.99%.

[0035] Specific Implementation Method Six: This implementation method differs from Specific Implementation Methods One to Five in that the diameter of the Al2O3 grinding ball mentioned in step ② is 20-30cm.

[0036] Specific Implementation Method Seven: This implementation method differs from Specific Implementation Methods One to Six in that: the working gas in step ④ is Ar with a purity of 99.99%, and the reaction gas is H2 with a purity of 99.99%.

[0037] Specific Implementation Method Eight: This implementation method differs from one of Specific Implementation Methods One to Seven in that the copper powder mentioned in step two has a purity of 99.9%, the particles are spherical, and the particle size is 40-60μm.

[0038] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Method Eight in that the copper powder has a purity of 99.9%, the particles are spherical, and the particle size is 50μm.

[0039] Specific Implementation Method 10: This implementation method differs from Specific Implementation Methods 1 to 9 in that the ball mill described in step 2 is a planetary ball mill.

[0040] Example 1:

[0041] The preparation method of the copper-coated graphene nanosheet-reinforced copper-based composite powder in this embodiment is carried out according to the following steps:

[0042] Step 1: Deposit a copper nanofilm on the surface of graphene nanosheets using a magnetron sputtering device to obtain copper nanocoated graphene nanosheet powder.

[0043] The graphene nanosheets described in step one have a purity of 99%, a diameter of 7 μm, a thickness of <100 nm, and a packing density of 0.08 g / mL.

[0044] The magnetron sputtering apparatus described in step one consists of a vacuum chamber, a magnetron sputtering particle stirring device, a heater 13, and a magnetron sputtering target 15. A magnetron sputtering target 15 is installed at the top of the vacuum chamber, and the magnetron sputtering target 15 is connected to the top wall of the vacuum chamber via a magnetron sputtering target telescopic rod 14. An air inlet 10 and an air outlet 11 are respectively installed on a pair of opposite side walls inside the vacuum chamber. A heater 13 is installed on the side wall of the vacuum chamber above the air inlet 10 and the air outlet 11, and the heater 13 is connected to a heater telescopic rod 12. The system is connected to the side wall of the vacuum chamber; the magnetron sputtering target 15 is located at the top of the vacuum chamber and is connected to the lower top surface of the vacuum chamber via a magnetron sputtering target telescopic rod 14; the heater telescopic rod 12 and the magnetron sputtering target telescopic rod 14 have length adjustment functions; the magnetron sputtering particle stirring device is located on the inner bottom surface of the vacuum chamber, and the magnetron sputtering particle stirring device consists of a detachable tray 1, stirring blades 2, strip baffles 3, hard bristles 4, positioning rods 6, a central shaft 7, and a connecting shaft 8. The detachable tray 1 has a retaining edge around its upper surface, and a boss 9 is located in the center of the detachable tray 1. Several stirring blades 2 are horizontally fixed radially on the side wall of the central shaft 7. The central shaft 7 is located on the upper surface of the boss 9, and a vertical through hole is located in the center of the boss 9. A connecting shaft 8 is located in the through hole, with its upper end connected to the central shaft 7 and its lower end connected to the power output shaft 5 of the drive motor. Several strip baffles 3 are provided on the lower surface of each stirring blade 2. The length gradually decreases from the end of the stirring blade 2 to the central shaft 7; a rigid bristle 4 arranged in a straight line is provided between two adjacent strip baffles 3 on the lower surface of the stirring blade 2; several positioning rods 6 are provided below the detachable storage tray 1, the upper end of the positioning rod 6 is set in the positioning hole on the lower surface of the detachable storage tray 1, and the lower end of the positioning rod 6 is fixed to the bottom of the vacuum chamber; the several positioning rods 6 are used to support and position the detachable storage tray 1; the lower end of the connecting shaft 8 is keyed to the power output shaft 5 of the drive motor;

[0045] The method for depositing a nano-copper film layer on the surface of graphene nanosheets using a magnetron sputtering device in step one is as follows:

[0046] ① Equipment preparation: Connect the pure copper target to the negative terminal of the target power supply, and connect the positive terminal of the target power supply to the vacuum chamber (chamber wall); the sputtering power supply is a DC-coupled high-power pulse power supply, with a DC current range of 5A, a pulse frequency range of 100Hz, a pulse width range of 50μs, and a pulse discharge voltage range of 100V; connect the placement tray to the negative terminal of the bias power supply, and connect the positive terminal of the bias power supply to the vacuum chamber. The bias power supply is a medium-frequency power supply with a constant frequency of 40KHz, a pulse width range of 10μs, and a voltage range of 50V;

[0047] The pure copper target is in sheet form and has a purity of 99.99%.

[0048] ② Sample preparation: Dry the graphene nanosheet powder in a drying oven for 2 hours, take out the dried graphene nanosheet powder and place it in a detachable tray 1, and add Al2O3 grinding balls to the tray. The mass ratio of powder to grinding balls is 1:8; the diameter of the Al2O3 grinding balls is 20cm.

[0049] ③ Pre-treatment before coating: Evacuate the vacuum chamber to a pressure of 8×10 -3 Heat and dry at 100℃ for 10 minutes, then evacuate again until the pressure reaches 8×10⁻⁶. -3 Pa, introduce working gas to a pressure of 10 Pa, and perform plasma sputtering cleaning for 10 min; set the rotation speed of stirring blade 2 to 5 r / min;

[0050] ④ Sputtering coating: Introduce working gas and reactive gas, both with a flow rate of 5 sccm. Turn on the power and perform magnetron sputtering coating for 30 minutes. The working gas is Ar with a purity of 99.99%, and the reactive gas is H2 with a purity of 99.99%.

[0051] Step 2: Use a ball mill to perform low-energy ball milling on the nano-copper-coated graphene nanosheet powder and copper powder to obtain nano-copper-coated graphene nanosheet-reinforced copper-based composite powder.

[0052] Step 2, the low-energy ball milling process, is as follows: copper powder and copper nano-coated graphene nanosheet powder are mixed at a mass ratio of 4:1 and then loaded into a ball mill jar; first, a vacuum is drawn, and then argon gas is introduced. The ball milling process is dry milling, the ball-to-material ratio is 8:1, the ball milling speed is 50 r / min, the ball milling time is 4 h, and the rotation is unidirectional, with a 10 min stop after every 1 h of ball milling.

[0053] The copper powder mentioned in step two has a purity of 99.9%, and the particles are spherical with a particle size of 40 μm.

[0054] The ball mill mentioned in step two is a planetary ball mill.

[0055] Figure 1This is a schematic diagram of the magnetron sputtering device in Example 1. In the figure, a is a grinding ball and b is the powder to be deposited. Figure 2 This is a top view of the stirring blade 2 and baffle 3 in the magnetron sputtering device of Example 1. Figure 3 This is an EDS image of the Cu element distribution in the copper-coated graphene nanosheet powder from Example 1. It can be seen that a dispersed copper film exists on the surface of the graphene nanosheets, with a large amount of dense copper film in a few areas, indicating that a large amount of dispersed copper film can be successfully grown on the graphene nanosheets using magnetron sputtering. Figure 4 The image shows a SEM image of the composite powder sample prepared in Example 1. It can be seen that the material is uniformly distributed in all regions of the composite powder, with no agglomeration.

[0056] Example 2:

[0057] The preparation method of the copper-coated graphene nanosheet-reinforced copper-based composite powder in this embodiment is carried out according to the following steps:

[0058] Step 1: Deposit a copper nanofilm on the surface of graphene nanosheets using a magnetron sputtering device to obtain copper nanocoated graphene nanosheet powder.

[0059] The graphene nanosheets described in step one have a purity of 99%, a sheet diameter of 8 μm, a thickness of <100 nm, and a packing density of 0.1 g / mL.

[0060] The magnetron sputtering apparatus described in step one consists of a vacuum chamber, a magnetron sputtering particle stirring device, a heater 13, and a magnetron sputtering target 15. A magnetron sputtering target 15 is installed at the top of the vacuum chamber, and the magnetron sputtering target 15 is connected to the top wall of the vacuum chamber via a magnetron sputtering target telescopic rod 14. An air inlet 10 and an air outlet 11 are respectively installed on a pair of opposite side walls inside the vacuum chamber. A heater 13 is installed on the side wall of the vacuum chamber above the air inlet 10 and the air outlet 11, and the heater 13 is connected to a heater telescopic rod 12. The system is connected to the side wall of the vacuum chamber; the magnetron sputtering target 15 is located at the top of the vacuum chamber and is connected to the lower top surface of the vacuum chamber via a magnetron sputtering target telescopic rod 14; the heater telescopic rod 12 and the magnetron sputtering target telescopic rod 14 have length adjustment functions; the magnetron sputtering particle stirring device is located on the inner bottom surface of the vacuum chamber, and the magnetron sputtering particle stirring device consists of a detachable tray 1, stirring blades 2, strip baffles 3, hard bristles 4, positioning rods 6, a central shaft 7, and a connecting shaft 8. The detachable tray 1 has a retaining edge around its upper surface, and a boss 9 is located in the center of the detachable tray 1. Several stirring blades 2 are horizontally fixed radially on the side wall of the central shaft 7. The central shaft 7 is located on the upper surface of the boss 9, and a vertical through hole is located in the center of the boss 9. A connecting shaft 8 is located in the through hole, with its upper end connected to the central shaft 7 and its lower end connected to the power output shaft 5 of the drive motor. Several strip baffles 3 are provided on the lower surface of each stirring blade 2. The length gradually decreases from the end of the stirring blade 2 to the central shaft 7; a rigid bristle 4 arranged in a straight line is provided between two adjacent strip baffles 3 on the lower surface of the stirring blade 2; several positioning rods 6 are provided below the detachable storage tray 1, the upper end of the positioning rod 6 is set in the positioning hole on the lower surface of the detachable storage tray 1, and the lower end of the positioning rod 6 is fixed to the bottom of the vacuum chamber; the several positioning rods 6 are used to support and position the detachable storage tray 1; the lower end of the connecting shaft 8 is keyed to the power output shaft 5 of the drive motor;

[0061] The method for depositing a nano-copper film layer on the surface of graphene nanosheets using a magnetron sputtering device in step one is as follows:

[0062] ① Equipment preparation: Connect the pure copper target to the negative terminal of the target power supply, and connect the positive terminal of the target power supply to the vacuum chamber (chamber wall); the sputtering power supply is a DC-coupled high-power pulse power supply, with a DC current range of 10A, a pulse frequency range of 500Hz, a pulse width range of 200μs, and a pulse discharge voltage range of 500V; connect the placement tray to the negative terminal of the bias power supply, and connect the positive terminal of the bias power supply to the vacuum chamber. The bias power supply is a medium-frequency power supply with a constant frequency of 40KHz, a pulse width range of 12μs, and a voltage range of 100V;

[0063] The pure copper target is in sheet form and has a purity of 99.99%.

[0064] ② Sample preparation: Dry the graphene nanosheet powder in a drying oven for 5 hours, take out the dried graphene nanosheet powder and place it in a detachable tray 1, and add Al2O3 grinding balls to the tray. The mass ratio of powder to grinding balls is 1:8; the diameter of the Al2O3 grinding balls is 25cm.

[0065] ③ Pre-treatment before coating: Evacuate the vacuum chamber to a pressure of 8×10 -3 Heat and dry at 100℃ for 30 minutes, then evacuate again until the pressure reaches 8×10⁻⁶. -3 Pa, introduce working gas to a pressure of 5 Pa, and perform plasma sputtering cleaning for 5 min; set the rotation speed of stirring blade 2 to 10 r / min;

[0066] ④ Sputtering coating: Introduce working gas and reactive gas, both with a flow rate of 20 sccm. Turn on the power and perform magnetron sputtering coating for 100 minutes. The working gas is Ar with a purity of 99.99%, and the reactive gas is H2 with a purity of 99.99%.

[0067] Step 2: Use a ball mill to perform low-energy ball milling on the nano-copper-coated graphene nanosheet powder and copper powder to obtain nano-copper-coated graphene nanosheet-reinforced copper-based composite powder.

[0068] Step 2, the low-energy ball milling process, is as follows: copper powder and copper nano-coated graphene nanosheet powder are mixed at a mass ratio of 8:1 and then loaded into a ball mill jar; first, a vacuum is drawn, then argon gas is introduced, the ball milling process is dry milling, the ball-to-material ratio is 10:1, the ball milling speed is 100 r / min, the ball milling time is 6 h, unidirectional rotation, and a 10 min stop after every 1 h of ball milling;

[0069] The copper powder mentioned in step two has a purity of 99.9%, and the particles are spherical with a particle size of 50 μm.

[0070] The ball mill mentioned in step two is a planetary ball mill.

[0071] In the copper-coated graphene nanosheet reinforced copper-based composite powder prepared in Example 2, a large number of dispersed copper films exist on the surface of the graphene nanosheets, and the material in each region of the powder is uniformly distributed without agglomeration.

[0072] Example 3:

[0073] The preparation method of the copper-coated graphene nanosheet-reinforced copper-based composite powder in this embodiment is carried out according to the following steps:

[0074] Step 1: Deposit a copper nanofilm on the surface of graphene nanosheets using a magnetron sputtering device to obtain copper nanocoated graphene nanosheet powder.

[0075] The graphene nanosheets described in step one have a purity of 99%, a diameter of 10 μm, a thickness of <100 nm, and a packing density of 0.12 g / mL.

[0076] The magnetron sputtering apparatus described in step one consists of a vacuum chamber, a magnetron sputtering particle stirring device, a heater 13, and a magnetron sputtering target 15. A magnetron sputtering target 15 is installed at the top of the vacuum chamber, and the magnetron sputtering target 15 is connected to the top wall of the vacuum chamber via a magnetron sputtering target telescopic rod 14. An air inlet 10 and an air outlet 11 are respectively installed on a pair of opposite side walls inside the vacuum chamber. A heater 13 is installed on the side wall of the vacuum chamber above the air inlet 10 and the air outlet 11, and the heater 13 is connected to a heater telescopic rod 12. The system is connected to the side wall of the vacuum chamber; the magnetron sputtering target 15 is located at the top of the vacuum chamber and is connected to the lower top surface of the vacuum chamber via a magnetron sputtering target telescopic rod 14; the heater telescopic rod 12 and the magnetron sputtering target telescopic rod 14 have length adjustment functions; the magnetron sputtering particle stirring device is located on the inner bottom surface of the vacuum chamber, and the magnetron sputtering particle stirring device consists of a detachable tray 1, stirring blades 2, strip baffles 3, hard bristles 4, positioning rods 6, a central shaft 7, and a connecting shaft 8. The detachable tray 1 has a retaining edge around its upper surface, and a boss 9 is located in the center of the detachable tray 1. Several stirring blades 2 are horizontally fixed radially on the side wall of the central shaft 7. The central shaft 7 is located on the upper surface of the boss 9, and a vertical through hole is located in the center of the boss 9. A connecting shaft 8 is located in the through hole, with its upper end connected to the central shaft 7 and its lower end connected to the power output shaft 5 of the drive motor. Several strip baffles 3 are provided on the lower surface of each stirring blade 2. The length gradually decreases from the end of the stirring blade 2 to the central shaft 7; a rigid bristle 4 arranged in a straight line is provided between two adjacent strip baffles 3 on the lower surface of the stirring blade 2; several positioning rods 6 are provided below the detachable storage tray 1, the upper end of the positioning rod 6 is set in the positioning hole on the lower surface of the detachable storage tray 1, and the lower end of the positioning rod 6 is fixed to the bottom of the vacuum chamber; the several positioning rods 6 are used to support and position the detachable storage tray 1; the lower end of the connecting shaft 8 is keyed to the power output shaft 5 of the drive motor;

[0077] The method for depositing a nano-copper film layer on the surface of graphene nanosheets using a magnetron sputtering device in step one is as follows:

[0078] ① Equipment preparation: Connect the pure copper target to the negative terminal of the target power supply, and connect the positive terminal of the target power supply to the vacuum chamber (chamber wall); the sputtering power supply is a DC-coupled high-power pulse power supply, with a DC current range of 15A, a pulse frequency range of 500Hz, a pulse width range of 500μs, and a pulse discharge voltage range of 1000V; connect the placement tray to the negative terminal of the bias power supply, and connect the positive terminal of the bias power supply to the vacuum chamber. The bias power supply is a medium-frequency power supply with a constant frequency of 40KHz, a pulse width range of 18μs, and a voltage range of 300V;

[0079] The pure copper target is in sheet form and has a purity of 99.99%.

[0080] ② Sample preparation: The graphene nanosheet powder was dried in a drying oven for 12 hours. The dried graphene nanosheet powder was then placed in a detachable tray 1, and Al2O3 grinding balls were added to the tray. The mass ratio of powder to grinding balls was 1:8. The diameter of the Al2O3 grinding balls was 28 cm.

[0081] ③ Pre-treatment before coating: Evacuate the vacuum chamber to a pressure of 8×10 -3 Heat and dry at 100℃ for 40 minutes, then evacuate again until the pressure reaches 8×10⁻⁶. -3 Pa, introduce working gas to a pressure of 0.5 Pa, and perform plasma sputtering cleaning for 40 min; set the rotation speed of stirring blade 2 to 15 r / min;

[0082] ④ Sputtering coating: Introduce working gas and reactive gas at a flow rate of 30 sccm, turn on the power, and perform magnetron sputtering coating for 500 min; the working gas is Ar with a purity of 99.99%, and the reactive gas is H2 with a purity of 99.99%.

[0083] Step 2: Use a ball mill to perform low-energy ball milling on the nano-copper-coated graphene nanosheet powder and copper powder to obtain nano-copper-coated graphene nanosheet-reinforced copper-based composite powder.

[0084] Step 2, the low-energy ball milling process, is as follows: copper powder and copper nano-coated graphene nanosheet powder are mixed at a mass ratio of 15:1 and then loaded into a ball mill jar; first, a vacuum is drawn, then argon gas is introduced, the ball milling process is dry milling, the ball-to-material ratio is 12:1, the ball milling speed is 200 r / min, the ball milling time is 5 h, unidirectional rotation, and a 10 min stop after every 1 h of ball milling;

[0085] The copper powder mentioned in step two has a purity of 99.9%, and the particles are spherical with a particle size of 55 μm.

[0086] The ball mill mentioned in step two is a planetary ball mill.

[0087] In the copper-coated graphene nanosheet reinforced copper-based composite powder prepared in Example 2, a large number of dispersed copper films exist on the surface of the graphene nanosheets, and the material in each region of the powder is uniformly distributed without agglomeration.

Claims

1. A method for preparing copper-based composite powder reinforced with copper nanosheets coated with graphene nanosheets, characterized in that: The preparation method of copper-coated graphene nanosheet-reinforced copper-based composite powder is carried out according to the following steps: Step 1: Deposit a copper nanofilm on the surface of graphene nanosheets using a magnetron sputtering device to obtain copper nanocoated graphene nanosheet powder. The magnetron sputtering device consists of a vacuum chamber, a magnetron sputtering particle stirring device, a heater (13), and a magnetron sputtering target (15). A magnetron sputtering target (15) is installed at the top of the vacuum chamber, and the magnetron sputtering target (15) is connected to the top wall of the vacuum chamber via a magnetron sputtering target telescopic rod (14). An air inlet (10) and an air outlet (11) are respectively installed on a pair of opposite side walls of the vacuum chamber. A heater (13) is installed on the side wall of the vacuum chamber above the air inlet (10) and the air outlet (11). (13) Connected to the side wall of the vacuum chamber via the heater telescopic rod (12); the magnetron sputtering target (15) is set at the top of the vacuum chamber, and the magnetron sputtering target (15) is connected to the lower top surface of the vacuum chamber via the magnetron sputtering target telescopic rod (14); the magnetron sputtering particle stirring device is set on the inner bottom surface of the vacuum chamber, and the magnetron sputtering particle stirring device consists of a detachable tray (1), stirring blades (2), strip baffles (3), hard bristles (4), positioning rods (6), central shaft (7), and connecting shaft ( 8) Composition; The upper surface of the detachable storage tray (1) is provided with a retaining edge around it. The center of the detachable storage tray (1) is provided with a boss (9). Several stirring blades (2) are horizontally fixed radially on the side wall of the central shaft (7). The central shaft (7) is provided on the upper surface of the boss (9). The center of the boss (9) is provided with a vertical through hole. The connecting shaft (8) is provided in the through hole. The upper end of the connecting shaft (8) is connected to the central shaft (7), and the lower end of the connecting shaft (8) is connected to the power output shaft (5) of the drive motor; Each Several strip baffles (3) are provided on the lower surface of the stirring blade (2). The length of the strip baffles (3) gradually decreases from the end of the stirring blade (2) to the central shaft (7). Hard bristles (4) are arranged in a straight line between two adjacent strip baffles (3) on the lower surface of the stirring blade (2). Several positioning rods (6) are provided below the detachable storage tray (1). The upper end of the positioning rod (6) is set in the positioning hole on the lower surface of the detachable storage tray (1), and the lower end of the positioning rod (6) is fixed to the bottom of the vacuum chamber. Step 2: Use a ball mill to perform low-energy ball milling on the nano-copper-coated graphene nanosheet powder and copper powder to obtain nano-copper-coated graphene nanosheet-reinforced copper-based composite powder. Step 2, the low-energy ball milling process, is as follows: copper powder and copper nano-coated graphene nanosheet powder are mixed at a mass ratio of 4 to 19:1 and then loaded into a ball mill jar; first, a vacuum is drawn, and then argon gas is introduced. The ball milling process is dry milling, the ball-to-material ratio is 8 to 12:1, the ball milling speed is 50 to 200 r / min, the ball milling time is 4 to 10 h, unidirectional rotation, and a 10 min stop after every 1 h of ball milling.

2. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 1, characterized in that: The graphene nanosheets described in step one have a purity of 99%, a diameter of 7-10 μm, a thickness of <100 nm, and a bulk density of 0.08-0.13 g / ml.

3. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 1, characterized in that: The lower end of the connecting shaft (8) mentioned in step one is keyed to the power output shaft (5) of the drive motor.

4. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 1, characterized in that: The method for depositing a nano-copper film layer on the surface of graphene nanosheets using a magnetron sputtering device as described in step one is as follows: ① Equipment preparation: Connect the pure copper target to the negative terminal of the target power supply, and connect the positive terminal of the target power supply to the vacuum chamber; the sputtering power supply is a DC-coupled high-power pulse power supply, with a DC current range of 0-20A, a pulse frequency range of 10-1000Hz, a pulse width range of 20-1000μs, and a pulse discharge voltage range of 0-2000V; connect the placement tray to the negative terminal of the bias power supply, and connect the positive terminal of the bias power supply to the vacuum chamber. The bias power supply is a medium-frequency power supply with a constant frequency of 40KHz, a pulse width range of 0-24μs, and a voltage range of 0-500V; ② Sample preparation: Dry the graphene nanosheet powder in a drying oven, take out the dried graphene nanosheet powder and place it in a detachable tray (1), and add Al2O3 grinding balls to the tray. The mass ratio of powder to grinding balls is 1:8-12. ③ Pre-treatment before coating: Evacuate the vacuum chamber to a pressure of 8×10 -3 Heat and dry at 80-150℃ for 10-60 minutes, then evacuate again to a pressure of 8×10⁻⁶ Pa. -3 Pa, introduce working gas to a pressure of 0.1-10 Pa, perform plasma sputtering cleaning for 5-60 min, and set the rotation speed of the stirring blade (2) to 5-20 r / min; ④ Sputtering coating: Introduce working gas and reactive gas, with a flow rate of 1-60 sccm for both. Turn on the power and perform magnetron sputtering coating for 1-3000 min.

5. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 4, characterized in that: The pure copper target mentioned in step ① is in sheet form and has a purity of 99.99%.

6. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 4, characterized in that: The diameter of the Al2O3 grinding ball mentioned in step ② is 20-30cm.

7. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 4, characterized in that: The working gas in step ④ is Ar with a purity of 99.99%, and the reaction gas is H2 with a purity of 99.99%.

8. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 1, characterized in that: The copper powder mentioned in step two has a purity of 99.9%, and the particles are spherical with a particle size of 40-60 μm.

9. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 8, characterized in that: The copper powder has a purity of 99.9%, and the particles are spherical with a particle size of 50 μm.

10. The method for preparing copper-coated graphene nanosheet-reinforced copper-based composite powder according to claim 1, characterized in that: The ball mill mentioned in step two is a planetary ball mill.

Citation Information

Patent Citations

  • Method for efficiently preparing graphene-reinforcing copper-based composite brazing filler metal at low temperature

    CN103817466A

  • Chemical-free production of graphene-reinforced inorganic matrix composites

    US20170225233A1